Journals of the Rev. Thomas Smith, and the Rev. Samuel Deane: pastors of the First church in Portland: with notes and biographical notices: and a Summary history of Portland - Smith, Thomas (J.S. Bailey, 1849)
Preface to the edition of 1849.-Memoir of the Rev. Thomas Smith.-Preface to the edition of 1821.-Extracts from Smith's journal [1720-1787]-Names of persons deceased, whose deaths are noticed in the journal.-State of the seasons,weather, &c. [1722-1787]-Extracts from the records of the First parish [1735-1809]-Memoir of the Rev. Samuel Deane.-Extracts from Dr. Deane's diary [1761-1814]-Buildings erected from 1784-1809.-Appendix. Memoir of Samuel Freeman. Summary history of Portland. Town officers. Index.